The Classification System and Characteristics of Coastal Landscapes in Quang Ngai Province - Ngoc, Dang Thi; Huan, Nguyen Cao; Hoi, Nguyen Dang; Truong, Tran Van; Dung, Ngo Trung (VNU Journal of Science: Earth and Environmental Sciences, 2020)
Studying coastal landscapes is an important and meaningful content in determining the natural and human properties of the territory and territorial sea, which is a valuable scientific basis for spatial planning in the economic development associated with the use of resources and environmental protection. The Quang Ngai’s coastal area is determined according to the continental boundary of 6 maritime districts/ cities and the boundary on the sea of the provincial coastal fishing zone. Coastal landscapes include terrestrial landscapes, marine landscapes, and island landscapes formed by the result of the interaction of natural components and human factors. The landscape structure of the coastal areas in Quang Ngai includes 1 system, 2 sub-systems, 3 classes, 6 sub-classes, 10 types, and 108 kinds of landscapes, In which, there are 75 kinds of terrestrial landscape, 27 kinds of marine landscape, and 6 kinds of the island landscape. The landscapes of the study area have differentiation from west to east (from the low mountain landscapes, hill - plain landscapes to marine landscapes and island landscapes) and from north to south, which is clearly represented in the differentiation of plain landscape kinds. The landscapes are highly variable, sensitive to external impacts, including development activities.